PENYULUHAN KESEHATAN PENCEGAHAN BULLYING SEBAGAI UPAYA MENJAGA KESEHATAN MENTAL REMAJA DI SMP N 01 WANASARI - Akbar Msaad; Rena Afita Sari; Widya Marta (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2025)
Bullying remains a prevalent social problem in school settings and has significant impacts on adolescents’ mental health, particularly among junior high school students. Adolescence is a developmental stage characterized by vulnerability to emotional and social pressures; therefore, experiences of bullying may adversely affect self-confidence, personality development, and psychological well-being. This community service activity aimed to increase students’ knowledge and awareness of bullying, its various forms in both school environments and digital media, as well as its effects on mental health. The activity was conducted at SMP Negeri 01 Wanasari Brebes on December 17, 2025, using educational counseling, interactive discussions, and question-and-answer sessions with a participatory approach. The results indicated an improvement in students’ understanding of bullying and mental health concepts, a positive change in attitudes toward the bystander effect, and increased awareness of reporting bullying incidents through the mechanisms that had been socialized. This activity contributed positively to fostering empathy, social awareness, and collective responsibility in creating a safe and supportive school environment for adolescents.